(untitled) (Research, Society and Development, 2022)
The present study aimed to identify and understand the challenges to provide adequate rehabilitation for post-Covid-19 patients. The research consisted of a descriptive-quantitative study, which used primary sources to obtain data. It was based on the application of an online questionnaire using multiple choice questions who the main audience was the physical therapists who attended/are attending patients with sequelae of Covid-19. The responses of 51 physiotherapists were analyzed and with the results obtained by the survey, it was possible to identify that there was an increase in demand for professional physiotherapists by patients who presented sequelae after Covid-19, mainly by those who had to stay in the Intensive Unit Care (ICU). Finally, it can be concluded that more research is needed to determine and establish a post Covid-19 rehabilitation program, as this is an extremely important approach, although the scenario is still new and discoveries are being made about the disease and its consequences.